Development of Video-Feedback System utilizing SMART system - attempt in private swimming club - Shimojo, H.; Sengoku, Y.; Sugimoto, S.; Miyaji, C.; Nomura, T. (1st International Scientific Conference of Aquatic Space Activities, 2008)
The purpose of the present study was to develop the Video-Feedback System (V-FBS) utilizing the SMART system in a private swimming club. The V-FBS is a system to provide feedback information along with underwater swimming motion during swimming training. The V-FBS utilization period was set for six-month. Eleven junior competitive swimmers attending in the private swimming club participated in this study (group utilizing the V-FBS: EX n=4, group merely taking part in the ordinary training session: CON n=7). Results of high attendance rate and larger training volume might indicate that the V-FBS could contribute to sustain the swimmers motivation to participate training. Questionnaires results indicated that swim image was recalled from the training diary and the movies for the swimmer. Consequently, we devised an ideal motor learning model for coaching field.